Intact cord resuscitation in newborns with congenital diaphragmatic hernia: insights from a lamb model - Teillet, Baptiste; Manœuvrier, Florian; Rougraff, Céline; Besengez, Capucine; Bernard, Laure; Wojtanowski, Anne; Ghesquieres, Louise; Storme, Laurent; Mur, Sébastien; Sharma, Dyuti; Le Duc, Kévin (Frontiers in Pediatrics, 2023)
Congenital diaphragmatic hernia (CDH) is a rare condition characterized by a pulmonary hypoplasia, vascular dystrophy, and pulmonary hypertension at birth. Validation of the lamb model as an accurate representation of human CDH is essential to translate research findings into clinical practice and understand disease mechanisms. This article emphasizes the importance of validating the lamb model to study CDH pathogenesis and develop innovative therapeutics. At 78 days of gestation, the fetal lamb's left forelimb was exposed through a midline laparotomy and hysterotomy and a sus-diaphragmatic thoracotomy was performed to allow the digestive organs to ascend into the thoracic cavity. At 138 +/-3 days of gestation, lambs were delivered via caesarean section then the lambs were mechanically ventilated with a gentle ventilation in pressure-controlled mode for two hours. CDH lambs exhibited lower left-lung-to-body-weight ratio 5.3 (2.03), p<0.05 and right-lung-to-body-weight ratio 8.2 (3.1), p<0.05. They reached lower Vt/kg (Tidal volume per kg) during all course of the resuscitation period with 1.2 (0.7) mL/kg at 10 min, 3 (1.65) mL/kg at 60 min (p<0.05). Compliance of the respiratory system was lower in CDH lambs with 0.5 (0.3) mL/cmH2O at 60 minutes (p<0.05) and 0.9 (0.26) mL/cmH2O at 120 minutes (p< 0.05) mL/cmH2O. Differences between pre-and postductal SpO2 was higher at 20 minutes 15.1 (21.4) %; and at 80 minutes 6.7 (14.5) % (p<0.05). CDH lambs had lower differences between inspired and expired oxygen fraction at 20 minutes, 4.55 (6.84) % and 60 minutes, 6.72 (8.57) (p<0.05). CDH lamb had lower left ventricle: 2.73 (0.5) g/kg (p<0.05) and lower right ventricle to left ventricle ratio (0.69 (0.8) p<0.05)). CDH lambs had significantly lower tidal volume compared to control lambs due to lower compliance of the respiratory system and higher airways resistances. These respiratory changes are characteristic of CDH infants and are associated with higher mortality rates. CDH lambs also exhibited pulmonary hypertension, pulmonary hypoplasia and left ventricle hypoplasia, also consistent with observations in human newborns. To conclude, our lamb model successfully provides a reliable representation of CDH and can be used to study its pathophysiology and potential interventions.